PENGHAMBATAN AKTIVITAS XANTHINE OXIDASE OLEH EKSTRAK ETANOL SARANG SEMUT (Myrmecodia tuberosa (non Jack) Bl.) SECARA IN VITRO - Ernawati Ernawati; Hari Susanti (Pharmaciana, 2014)
Uric acid is the end product of purine metabolism that can settle in the joints and form smallcrystals, causing inflammation known as gout. Gout is a disease caused by high levels of uric acid inthe blood (hyperuricemia). One of the drugs used to treat gout was allopurinol to inhibite the activityof xanthine oxidase mechanism. Myrmecodia tuberosa (non Jack) Bl. known to contain flavonoids andempirically proven to treat rheumatic complaints and gout. Therefore, research needs to examinewhether the ethanol extract of the sarang semut to inhibite xanthine oxidase activity. Allopurinol isused as a comparison. The active substances of the Myrmecodia tuberosa (non Jack) Bl. was extractedwith ethanol using maceration method after soaked with petroleum ether. The xanthine oxidaseinhibitor activity of the Myrmecodia tuberosa (non Jack) Bl production ethanol extract wasspectrophotometrically determined by monitoring the reducing of uric acid at a wavelength(Î») 295 nm with xanthine as substrate. Rate values obtained subsequently used to calculate the valueof the activity. Then determined the concentration of the ethanol extract can inhibit the activity ofof xanthine oxidase by 50% (IC50). The results of the research showed that the ethanol extracts of sarang semut inhibited xanthine oxidase activity with IC50 112.40 Âµg/ml, while allopurinol was3.16 Âµg/ml.